2016
DOI: 10.1245/s10434-016-5373-2
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Resection Rates and Clinical Outcomes After FOLFIRINOX-Based Treatment in Patients with Locally Advanced Pancreatic Cancer

Abstract: BackgroundFOLFIRINOX prolongs survival in patients with metastatic pancreatic cancer and may also benefit patients with locally advanced pancreatic cancer (LAPC). Furthermore, it may downstage a proportion of LAPC into (borderline) resectable disease, however data are lacking. This review assessed outcomes after FOLFIRINOX-based therapy in LAPC.MethodsThe PubMed, EMBASE and Cochrane library databases were systematically searched for studies published to 31 August 2015. Primary outcome was the (R0) resection ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(61 citation statements)
references
References 29 publications
2
59
0
Order By: Relevance
“…The vast majority of patients (90%) were treated with a modified FOLFIRINOX regimen and a median number of 8 cycles (IQR 5-9). Nonetheless, the median OS rate of 14.8 months and 9.0 months, for LAPC and MPC respectively, were similar to the OS rates reported by studies with a lower percentage of dose modifications (14%) and a higher median number of cycles (10 cycles) 5 , 10 . Moreover, the response rate of 26% seen in our patient population is comparable to previous reports of this regimen 5 .…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The vast majority of patients (90%) were treated with a modified FOLFIRINOX regimen and a median number of 8 cycles (IQR 5-9). Nonetheless, the median OS rate of 14.8 months and 9.0 months, for LAPC and MPC respectively, were similar to the OS rates reported by studies with a lower percentage of dose modifications (14%) and a higher median number of cycles (10 cycles) 5 , 10 . Moreover, the response rate of 26% seen in our patient population is comparable to previous reports of this regimen 5 .…”
Section: Discussionsupporting
confidence: 84%
“…Our study, however, demonstrated that the majority of grade 3-4 complications related to FOLFIRINOX resolved by dose reduction (Figure 1 ). Our cohort furthermore suggests that, regardless of the dose reductions, patients can still benefit from FOLFIRINOX with survival rates comparable to the study of Conroy et al 5 , 10 .…”
Section: Discussionsupporting
confidence: 81%
“…The resection rates for upfront resectable and LAPC have increased over the past 3 decades, with associated improvement in survival. 4 , 5 , 6 Such improvements have been attributed, in part, to surgery at high-volume facilities (HVFs), likely as a result of higher margin negative resection rates, comprehensive lymph node dissections, lower perioperative mortality, and increased use of adjuvant therapy compared with low volume facilities (LVFs). 7 , 8 , 9 Hospital volume, more than individual surgeon experience, has been associated with improved clinical outcomes, which may be explained by the availability of multidisciplinary management teams at such facilities.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review on clinical outcomes after FOLFIRINOX-based treatment for LA-PDAC demonstrated a 28% resection rate, of which 77% were R0, and a median overall survival ranging between 8.9 and 25.0 months. [ 14 ] These data suggest that FOLFIRINOX-based treatment is indeed a promising option for patients with LA-PDAC, with acceptable toxicity (23% Grade 3–4 complications). Future unselected prospective cohort studies are needed to determine the exact role for FOLFIRINOX in LA-PDAC.…”
Section: Locally Advanced Pancreatic Cancermentioning
confidence: 91%